Застосування апарату нечіткої логіки для оптимізації систем зрошення в сільському господарстві - Зінов’єва, Ольга Геннадіївна; Zinovieva, Olha (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: Сучасне сільське господарство стикається із численними викликами, серед яких – зміна клімату, дефіцит води та потреба в підвищенні врожайності. У зв’язку із цим системи зрошення стають ключовим фактором для забезпечення стійкого агровиробництва. У статті досліджується застосування алгоритму нечіткого логічного висновку Мамдані для оптимізації систем автоматизованого зрошення сільськогосподарських культур. Запропоновано нечітку модель керування процесом поливу з використанням експертних знань агрономів. Наведено приклади побудови функцій належності для основних лінгвістичних змінних, продемонстровано процес фазифікації та формування правил типу «ЯКЩО – ТО». Модель дає змогу визначати оптимальний обсяг поливу з урахуванням вологості ґрунту, температури повітря та ймовірності опадів. Розглянуто приклад практичного обчислення інтенсивності зрошення й описано переваги використання алгоритму Мамдані порівняно з традиційними методами. Використання цього алгоритму дає змогу поліпшити управління водними ресурсами, скоротити затрати й підвищити ефективність руйнування. /// EN: This paper investigates the application of the Mamdani fuzzy inference algorithm for optimizing automated irrigation systems in agricultural crop production. The study addresses the critical problem of inefficient water resource utilization and the necessity for adaptive irrigation management that accounts for multiple variable factors. Modern agriculture faces unprecedented water scarcity challenges, with irrigation consuming approximately 70% of global freshwater resources, much of which is wasted due to inadequate control systems. The study presents a conceptual model of an irrigation management system based on Mamdani-type fuzzy inference. The system uses linguistic input variables – soil moisture (very low, low, medium, high, very high), air temperature (low, moderate, high, very high), air humidity (low, moderate, high), and precipitation forecast (none, weak, moderate, strong) – to determine the output variable, irrigation intensity (none, minimum, moderate, heavy, maximum). Triangular and trapezoidal membership functions are defined for fuzzification, while the centroid method is used for defuzzification. A practical example of rule formation and inference is given to illustrate the adaptive nature of the approach Simulation and field-level studies referenced in this paper demonstrate that fuzzy-based irrigation control can reduce water consumption by up to 30 % without compromising crop yield. The Mamdani model’s main advantage lies in its interpretability: rules are easily constructed using expert agronomic knowledge, allowing transparent system behavior and easier calibration for local conditions. The proposed methodology contributes to the broader field of precision agriculture and smart farming, supporting efficient use of water resources and environmental sustainability. Future work should focus on integrating fuzzy logic with machine learning algorithms for automatic tuning of membership functions and rules, and on validating such systems under diverse agro-climatic conditions in Ukraine and beyond.
Application of fuzzy logic apparatus for optimization of irrigation systems in agricultur
Keywords: нечітка логіка; оптимізація зрошення; алгоритм Мамдані; автоматизація сільського господарства; інтелектуальні системи; fuzzy logic; irrigation optimization; Mamdani algorithm; agricultural automation; intelligent systems